2011
DOI: 10.1108/09654281111161202
|View full text |Cite
|
Sign up to set email alerts
|

Filling the black box of implementation for health‐promoting schools

Abstract: Purpose -Achieving organisational learning and greater specificity for implementation action for health-promoting schools requires detailed understanding of the necessary components. They include: preparing and planning for school development, policy and institutional anchoring, professional development and learning, leadership and management practices, relational and organisational context, student participation, partnerships and networking, and sustainability. This paper seeks to elaborate a theoretically ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 42 publications
(53 reference statements)
6
83
0
5
Order By: Relevance
“…In terms of staff training, which is very important (Jourdan, 2011) , 70% of the SPHE teachers had been trained, which still left a deficit of 30% untrained. A designated team to develop and implement HPS has been identified as critical (Firth et al, 2008;Rowling and Samdal, 2011). The Australian experience identified that successful teams had certain characteristics which included, inclusion of management, holding regular meetings in school time, drawing team members from a range of areas within the school, retaining most of the members over at least three years and having clear roles within the team as well as shared responsibility (Firth et al, 2008).…”
Section: Policy and Planningmentioning
confidence: 99%
“…In terms of staff training, which is very important (Jourdan, 2011) , 70% of the SPHE teachers had been trained, which still left a deficit of 30% untrained. A designated team to develop and implement HPS has been identified as critical (Firth et al, 2008;Rowling and Samdal, 2011). The Australian experience identified that successful teams had certain characteristics which included, inclusion of management, holding regular meetings in school time, drawing team members from a range of areas within the school, retaining most of the members over at least three years and having clear roles within the team as well as shared responsibility (Firth et al, 2008).…”
Section: Policy and Planningmentioning
confidence: 99%
“…This study provides insight into factors influencing the implementation of HPS practices across the province of NS and adds to the growing evidence that suggests that context is a critical feature in understanding the dissemination and sustainability of the HPS approach (Rowling & Jeffreys, 2006;Rowling & Samdal, 2011). Policies and practices were inherently influenced by characteristics unique to individual schools, which have been previously shown to influence the implementation of change, or an innovation (like HPS) in schools (Hall & Hord, 1987;Payne, Gottfredson, & Gottfredson, 2006).…”
Section: Discussionmentioning
confidence: 81%
“…Research has shown that educators, the essential supporters of HPS, are often concerned with seeking practical solutions and gaining new knowledge that meets their situational needs, organizational circumstance and stage of growth (Boot, van Assema, Hesdahl, & de Vries, 2010;Butler et al, 2008;Mohammadi et al, 2010;Rowling & Jeffreys, 2006). Features related to organizational context, such as capacity and school culture, have also been cited as critical to HPS success and sustainability (Rowling & Jeffreys, 2006;Rowling & Samdal, 2011). Therefore, it is essential to understand the interaction between the practical features (i.e., what is being done), the functional processes (i.e., how it is being done) and the contextual environment of schools in relation to HPS implementation.…”
mentioning
confidence: 98%
“…Another key determinant of the success appears to be effective implementation (Barry and Jenkins, 2007;Rowling and Samdal, 2011). Many studies show that complete and accurate implementation leads to more positive outcomes, suggesting that fidelity to programmes is important.…”
Section: Mindfulness Friends For Lifementioning
confidence: 99%